Bling - Kennedy, Erica (New York : Miramax Books, 2003)
Cinderella remixed: an uninhibited, unputdownable novel about a small-town girl and the music mogul determined to turn her into a megastar.
Keywords: African American women singers -- Fiction; Sound recording industry -- Fiction; New York (N.Y.) -- Fiction; Musical fiction